Penggunaan Alat Bukti Elektronik dalam Menyelesaikan Sengketa Hukum Perdata di Indonesia - Monica Maharani Dewi; Tarisa Dinar Alifia; Sebastian Sitohang (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Proving civil cases involving electronic documents and information electronic evidence which is now legalized has become electronic evidence that can be trusted (legitimate) and has been regulated in Article 1866 of the Civil Code in conjunction with Article 184 HIR in conjunction with Article 5 paragraph (1) and paragraph (2) Law Number 11 of 2008 concerning ITE. Panel of Judges in assess whether electronic information is Electronic Evidence valid based on a digital forensic assessment. Even though it is related to assessment procedures electronic evidence using digital forensics is regulated in the ITE Law and Law others, but in civil trial practice the method is not necessarily used digital forensics because there are technical obstacles. Additionally, Law Civil Procedure in Indonesia has not improved specifically regarding electronic evidence in civil evidence. So there is no procedure that regulates how how to present electronic evidence in civil trials. Without it yet This regulation actually results in legal uncertainty regarding the procedures These electronic devices are shown in civil trials. Given that there are obstacles in judicial practice, the State must immediately carry out reforms Civil Procedure Law in Indonesia regarding electronic evidence, can do this renewal of the evidence system to accommodate developments in evidence electronic documents submitted by the parties during the trial.